Adopting the principal instructional management rating scale for enhancing instructional delivery in Nigerian schools - Bada, Hafsat Aliyu; Yusuf, Habibat Abubakar; Oladele, Jumoke Iyabode; Oloba, Peter Babajide (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study explores the validation and application of the principal instructional management rating scale (PIMRS) for enhancing instructional leadership in Nigerian secondary schools. This was achieved by checking its content, face, construct, and reliability, with a focus on how clear the language was and how it related to culture. A sample of 100 secondary school teachers from four schools in North-Central Nigeria participated in this research. Expert reviews ensured content validity, while the instrument demonstrated high reliability, with an overall Cronbach’s alpha coefficient of 0.95. The subscales for the three dimensions achieved acceptable reliability: 0.83 for defining the school mission (DSM), 0.87 for managing the instructional program (MIP), and 0.91 for shaping the school learning climate (SLC). The results also showed strong positive relationships between the PIMRS dimensions, which supports the tool’s usefulness for evaluating how Nigerian schools handle instructional leadership. This study provides a robust foundation for further research on instructional leadership in Nigeria and offers a validated tool to improve school leadership practices, enhance instructional delivery, and ultimately foster student achievement. The adoption of the PIMRS in Nigerian secondary schools has the potential to drive systemic improvements in school effectiveness and instructional leadership. The findings suggest refining the sub-scales of monitoring halls, venues, and instructional feedback to teachers (IFT) for enhanced reliability. Additionally, capacity-building workshops for principals and integration of PIMRS into leadership training programs, as well as policy adoption for standardized evaluation, are essential for successful implementation and improved instructional leadership.